Aggregation territory formation and cell streaming in a model of the cellular slime mould Dictyostelium discoideum - Höfer, T; Maini, P (1996)
A reaction-diffusion-advection model of multicellular morphogenesis during in the aggregation phase of the microorganism Dictyostelium discoideum is reviewed. Linear analysis identifies a novel chemotaxis-driven instability which appears to underlie the cell streaming phenomenon observed experimentally. Numerical simulations show that the model captures in considerable detail the establishment of aggregation territories and the formation of branching cell stream patterns which characterize aggregation in situ.